Participating in God's Purpose by Following the Cruciform Pattern of Christ The Use of Psalm 69:9b in Romans 15:3 - Wu, Siu Fung (2015)
In his letter to the Romans, Paul emphasizes the importance of Israel's Scripture for his gospel (1:3-4; 16:25-27). In 15:4, he specifically links the Scriptures with endurance, consolation, and hope. Immediately before this verse, Paul cites Ps 69:9b. Commentators customarily—and rightly—think that Paul uses this citation to support his exhortation on community harmony in Rom 14-15. But is this the sole function of the citation? Does it, directly or indirectly, support other themes in Romans? Psalm 69 is significant for Romans, because it is cited in 11:9-10 and 15:3. It is also probable that Ps 69 played a significant role in the early church's understanding of Christ's suffering and death, because it is alluded to in the passion narratives in all four canonical gospels. But the use of Ps 69:9b in Rom 15:3 has drawn relatively little attention among scholars. This article suggests that the function of the citation is extensive, and it strengthens several main themes of the letter. More specifically, this article argues that the citation serves to reinforce Paul's call for believers to participate in God's purpose by following the cruciform pattern of Christ.
Keywords: Bibel; Bibel; Audiences; Christianity; Endurance; Eschatology; Laments; Obedience; Prayer; Psalms